Kompetensi Kewirausahaan Mahasiswa Jurusan Ilmu Kesejahteraan Keluarga Konsentrasi Tata Boga Universitas Negeri Padang - Istiq Riolita Asral; Asmar Yulastri (Universitas Negeri Padang, 2020)
This study aims to describe the entrepreneurial competence of Culinary Arts Students, Padang State University. This research is a quantitative descriptive study. The population of this research is Culinary Arts Students, Tourism and Hospitality Faculty, Padang State University 2016 and 2017 who have passed entrepreneurship courses as many as 174 people taken based on proportional random sampling technique with a sample of 64 people. Data collection techniques are carried out by distributing objective test sheets. Data were analyzed through descriptive analysis with the assessment categorization method based on the average score and percentage of ratings. The results of this study indicate that student entrepreneurship competencies with an average of 67.17 are in the high category. This means that the entrepreneurial competence of Culinary Arts Concentration Students at the State University of Padang is quite maximum to conduct entrepreneurship.